M191. EFFECT OF BREXPIPRAZOLE ON ENGAGEMENT IN PATIENTS WITH SCHIZOPHRENIA: POST-HOC ANALYSIS OF THREE STUDIES. (18th May 2020) - Ismail, Zahinoor; Pedersen, Anne M; Thase, Michael E; Rasmussen Meehan, Stine; Weiss, Catherine; Groes Larsen, Klaus; Chen, Dalei; Nylander, Anna-Greta; Baker, Ross A; McIntyre, Roger
Abstract: Background: In schizophrenia, a patient's quality of life and level of psychosocial functioning is dependent on two key domains: the severity of their psychotic symptoms, and the side effects of antipsychotic medication. In addition, people with schizophrenia experience motivation deficits, thus patient engagement is a key component of successful schizophrenia treatment outcomes. The present analyses investigated the effect of brexpiprazole (a serotonin–dopamine activity modulator that is a partial agonist at 5-HT1A and dopamine D2 receptors, and an antagonist at 5-HT2A and noradrenaline alpha1B/2C receptors, all at similar potency) on patient engagement. The concept of patient engagement stems from the collective post-marketing experience with brexpiprazole, and has been established in patients with MDD and an inadequate response to antidepressant treatments treated with adjunctive brexpiprazole. To explore the concept of engagement in schizophrenia, 11 out of the 30 items in the Positive and Negative Syndrome Scale (PANSS) were identified as relevant to capture patient improvement and well-being beyond an improvement of the core symptoms of schizophrenia. Methods: The studies [Vector (NCT01396421), Beacon (NCT01393613) and Lighthouse (NCT01810380)] included patients aged 18–65 years experiencing an acute exacerbation of schizophrenia (DSM-IV-TR criteria), and who would benefit from hospitalization or continued hospitalization. Eligible patients were randomized to 6 weeks treatment with placebo or brexpiprazole ranging from doses of 0.25 to 4 mg/day depending on the study. The primary efficacy analysis in all three studies was the mean change in PANSS Total score from baseline (randomization) to Week 6. The PANSS was administered at weekly intervals. Items N1, N2, N3, N4, N5, N6, G6, G7, G13, G15, and G16 were selected from the PANSS as relevant items to capture patient engagement. In the present analysis, data were pooled for patients allocated to placebo and to a brexpiprazole dose in the range of 2–4 mg. Mean changes from baseline on the selected PANSS items were analyzed using a mixed model repeated measures approach. A Principal Component Analysis (PCA) was performed to validate whether changes in the selected items clustered together. Standardized effect sizes were also calculated. Results: In the short-term studies, the PANSS scale was completed at baseline by a total of 1, 378 patients, brexpiprazole 2–4 mg (n=863); placebo (n=515). At Week 6, an improvement (p<0.05) was observed on 10 out of the 11 selected items from the PANSS scale, with LS mean differences versus placebo in the range of -0.11 to -0.24. The PCA showed that the majority of the selected items cluster together, confirming the importance of the selected items for patient engagement/re-engagement with their lives. The standardized effect size for brexpiprazole versus placebo was -0.31 for the combined 11 selected items and of a similar magnitude as the effect size of the PANSS Total score (-0.32). Discussion: 11 items from the PANSS scale were selected to capture patient re-engagement. The clustering, as shown by the PCA, validated the selection of the specific engagement items. The results of these exploratory post-hoc analyses suggest that treatment with brexpiprazole, in addition to improving symptoms of schizophrenia, has the potential to also improve patient well-being and engagement with life.